| 132 | where |

| 133 | [[latex(F_{i+1/2}=\frac{3-R_{2,i+1/2}}{8} \left(v_{i}^n+v_{i+1}^n \right ) \left ( E^n_i+E^n_{i+1/2} \right ) )]] |

| 134 | |

| 135 | where |

| 136 | |

| 137 | [[latex(R_{2,i+1/2} = \lambda_{i+1/2}+\lambda_{i+1/2}^2 R_{i+1/2}^2)]] |

| 138 | and |

| 139 | [[latex(R_{i+1/2} = \frac{\left | E^n_{i+1}-E^n_{i} \right | }{2 \kappa_{i+1/2} \left ( E^n_i+E^n_{i+1} \right )})]] |

| 140 | |

| 141 | and |

| 142 | [[latex(\kappa_{i+1/2} = \frac{\kappa^n_{i}+\kappa^n_{i+1}}{2} \mbox{ and } \lambda_{i+1/2} = \frac{1}{R_{i+1/2}} \left ( \coth R_{i+1/2} - \frac{1}{R_{i+1/2}} \right ) )]] |

| 143 | |

| 144 | and |

| 145 | |

| 146 | [[latex(\lambda_{i} = \frac{1}{R_{i}} \left ( \coth R_{i} - \frac{1}{R_{i}} \right ) )]] |

| 147 | |

| 148 | and |

| 149 | [[latex(R_{i} = \frac{\left | E^n_{i+1}-E^n_{i-1} \right | }{4 \kappa_{i} \left ( E^n_{i-1}+E^n_{i+1} \right )})]] |

| 150 | |